2017
DOI: 10.18240/ijo.2017.02.01
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory effects of asiatic acid in lipopolysaccharide-stimulated human corneal epithelial cells

Abstract: AA decreases the generation of inflammatory factors IL-8, IL-6, IL-1β, TNF-α, and TGF-β in LPS-stimulated HCECs. AA significantly inhibites the intracellular concentrations of ROS and increases GSH generation. AA also inhibites LPS-induced p-Akt in HCECs. These findings reveal that AA has anti-inflammation effects in LPS-stimulated HCECs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Treatments that reduce oxidative stress in RGCs may be a novel therapeutic strategy for glaucoma; however, no effective neuroprotectants are available to be applied as a treatment for glaucoma. AA was reported to possess antioxidant, anti-inflammatory, and antiexcitotoxic properties and to improve mitochondrial function ( Huang et al, 2016 ; Chen et al, 2017 ; Nataraj et al, 2017 ) and is thus believed to target multiple mechanisms underlying glaucoma development. In humans, elevated IOP is the major risk factor for glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Treatments that reduce oxidative stress in RGCs may be a novel therapeutic strategy for glaucoma; however, no effective neuroprotectants are available to be applied as a treatment for glaucoma. AA was reported to possess antioxidant, anti-inflammatory, and antiexcitotoxic properties and to improve mitochondrial function ( Huang et al, 2016 ; Chen et al, 2017 ; Nataraj et al, 2017 ) and is thus believed to target multiple mechanisms underlying glaucoma development. In humans, elevated IOP is the major risk factor for glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…Extreme environments including hyperglycaemic and hyperosmolar environments may cause excess ROS accumulation, which is considered an upstream suppressor of the EGFR-mediated PI3K/AKT signalling pathway, and delays healing of the CE [ 60 ]. In vitro and in vivo studies have shown that inhibition of ROS production reactivates PI3K/AKT signalling, which decreases apoptosis and inflammation in CECs [ 22 , 23 ]. Furthermore, the expression of the cellular tumour antigen P53, a PI3K/AKT substrate, is upregulated by ROS in hCECs [ 61 , 62 ].…”
Section: Interactions Between Ros and Akt In Cecsmentioning
confidence: 99%
“…Importantly, dysregulation of CE homeostasis caused by impaired CEC responses is associated with many corneal diseases, such as DK, DED, and keratitis [ 18 , 20 , 21 ]. Therefore, an in-depth understanding of the pathophysiology of CE with a focus on the PI3K/AKT signalling pathway is important for maintaining the integrity of patients’ corneas and seeking reliable treatments and new drugs [ 22 , 23 ]. In this review, we provide evidence for the regulatory role of the PI3K/AKT signalling pathway in CECs to support its clinical application.…”
Section: Introductionmentioning
confidence: 99%
“…AA in HaCaT cells reduced glycative stress by blocking AGE-RAGE interaction, inhibiting MAPK pathway and MMP expression along with amelioration of oxidative and inflammatory stress. AA also exhibited potent free radical scavenging property and inhibited pro-inflammatory cytokines against LPS-induced inflammatory response in human corneal epithelial cells (Chen et al, 2017 ). It also inhibited LPS-induced p-Akt and TGF-β and retained glutathione levels.…”
Section: Asiatic Acid In Photoagingmentioning
confidence: 99%